Analisis Miskonsepsi Siswa Kelas X.3 SMAN 1 Belopa pada Materi Pokok Ikatan - Tutiana Tutiana; Muharram Muharram; Halimah Husain (ChemEdu, 2022)
This study is a descriptive research which aimed to find out the misconceptions study on chemical bond. The samples in this research is the class X.3 SMA Negeri 1 Belopa as much 36 students. The data was collected by instrument which has 20 items two-tier multiple choice, observation page for teacher, student, and study source and interview to identified cause of misconception. The data was analyzed by descriptive statistic method to obtain percentage of the misconceptions in each item. There is six subconcept that analyzed. The result of this research showed that percentage misconceptions of students average to learning of chemical bond is 11,29 % and low category. Percentage misconceptions of students to element preference to stable is 18,52%; draw of Lewis structure is 9,26%; formation of ion bond is 11,11%; formation of covalent bond is 15,00 %; formation of covalent coordination is 13,89%. The result research show that misconception causes by, 1) teacher not give detailed explanation and 2) student is praconception is wrong